Trainees’ perspectives on sickle cell education: a qualitative needs assessment - Elizabeth J. Prince; Katherine J. Feder; Cecelia Calhoun; Alfred I. Lee; C. Patrick Carroll; Valentina Restrepo; Layla Van Doren (BMC Medical Education, 2024)
Abstract Background Sickle cell disease (SCD) exemplifies many of the social, racial, and healthcare equity issues in the United States. Despite its high morbidity, mortality, and cost of care, SCD has not been prioritized in research and clinical teaching, resulting in under-trained clinicians and a poor evidence base for managing complications of the disease. This study aimed to perform a needs assessment, examining the perspectives of medical trainees pursuing hematology/oncology subspecialty training regarding SCD-focused education and clinical care. Method Inductive, iterative thematic analysis was used to explore qualitative interviews of subspecialty hematology-oncology trainees’ attitudes and preferences for education on the management of patients with SCD. Fifteen trainees from six programs in the United States participated in 4 focus groups between April and May 2023. Results Thematic analysis resulted in 3 themes: 1. Discomfort caring for patients with SCD. 2. Challenges managing complications of SCD, and 3. Desire for SCD specific education. Patient care challenges included the complexity of managing SCD complications, limited evidence to guide practice, and healthcare bias. Skill-building challenges included lack of longitudinal exposure, access to expert clinicians, and didactics. Conclusions Variations in exposure, limited formal didactics, and a lack of national standardization for SCD education during training contributes to trainees' discomfort and challenges in managing SCD, which in turn, contribute to decreased interest in entering the SCD workforce. The findings underscore the need for ACGME competency amendments, dedicated SCD rotations, and standardized didactics to address the gaps in SCD education. Graphical Abstract